Upaya Meningkatkan Prestasi Belajar IPA Materi Perubahan Bentuk Benda melalui Penggunaan Alat Peraga pada Siswa Kelas VI SD Negeri 1 Sukowetan Semester I Tahun Pelajaran 2014/2015 - Priyanto, Priyanto (Taallum: Jurnal Pendidikan Islam, 2016)
During this time, there are still many teachers who likens the learning process with students as blank paper and still found a teacher who suppress learning through rote formulas and specific strategies to solve specific problems so that the knowledge gained survive only in short-term memory of the child. Learning through the use of props at SDN 1 Sukowetan encourage students to make observations on an object independently, to train students to learn to find new ideas and their relationships with the concepts that have been known, and can increase the concentration of learning and student learning outcomes. It can be seen from the observation of students in learning activities changes in the shapes of objects through the use of props that have increased as well as the completeness achieved from 60% in the first cycle increased to 90% in the second cycle.